Collisions of the Personal and the Professional: How Frontline Welfare Workers Manage Carceral Citizens. Issue 1 (February 2020) - Welsh, Megan; Leyva, Kristina
For criminalized people, particularly those who have been recently incarcerated, applying for and maintaining public assistance—cash aid and/or food assistance—is an immediate and crucial element of survival. Yet relative to a substantial body of research that documents pathways into and out of carceral citizenship, this aspect of postincarceration work has received little scholarly attention. Likewise, frontline welfare workers are often simplistically portrayed as gatekeepers who restrict poor people's access to public assistance. In this article, we make visible the intersection of welfare and criminal-legal involvement by examining how criminalized clients are understood by welfare workers in one large, densely populated California county. Our data come from a larger ethnographic study of women's postincarceration experiences of public institutions and include in-depth interviews with 19 frontline welfare workers and participant observation of welfare offices. We find that (a) criminal-legal awareness varies among welfare workers; (b) workers engage in substantial invisible labor, in large part to counteract the carceral logics of the welfare system; and (c) in absence of professional training, workers draw heavily on their own situated knowledge to manage the challenges of their work. Contextualizing these findings within a broader trend toward the deprofessionalization of welfare workers, we argue that the training and education of this workforce, particularly around criminal-legal issues, is an important avenue for social work advocacy.